ASSESSING ANTICOAGULATION SAFETY AND EFFICACY IN ANTIPHOSPHOLIPID SYNDROME PATIENTS MONITORED BY FACTOR II ACTIVITY ASSAY - CHRISTOPHER, AMY; Sweet, Michelle (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To determine if monitoring antiphospholipid syndrome (APS) patients on warfarin by factor II activity assay (FIIAA) would decrease thrombus risk or if elevating international normalized ratio (INR) goal based on FIIAA would increase bleeding risk. Methods: A community hospital retrospective chart review was conducted on anticoagulation clinic APS patients (n=49) over 50 months. Patients with an APS-associated diagnosis compliant warfarin therapy were included as long as they were at least 18 years of age. Patients were excluded if they were monitored in the clinic for <6 months, became pregnant, or developed cancer during the study period. The primary outcome was to determine if FIIAA monitoring reduced thrombus risk or increased bleeding risk. Results: No statistical difference in bleeding event, age, comorbidities, or sex was determined between the FIIAA monitored and non-FIIAA monitored group. Thromboembolic events approached statistical significance (p=0.053) in the monitored group. Two of the 3 patients had a subtherapeutic INR and one had additional thrombophilias. Conclusion: Thromboembolic risk was not reduced by FIIAA monitoring in APS patients. INR goal increases based on FIIAA monitoring did not increase bleeding risk. A larger study may help determine the most appropriate way to monitor APS patients using warfarin. Keywords: Antiphospholipid syndrome, Factor II activity assay, Warfarin, Thrombosis, Anticoagulation and bleeding. Â